Efektivitas teh daun sentalo ( Chromolaena odorataa Linn) menurunkan kadar glukosa darah pada tikus putih jantan - Nurlaila Agustikawati; Desy Fadilah Adina Putri; Iga Maliga (Jurnal Penelitian Pendidikan IPA, 2021)
Traditional medicine cannot be removed from the lives of Indonesian people. In addition to very minimal side effects, traditional medicine using natural ingredients is widely used by the Sumbawa people because it is easy to obtain, easy to process, economical and has been carried out for generations. One of the natural ingredients that are widely used is sentalo leaf. This leaf is widely used as a medicine for torn wounds to stop the bleeding that occurs. Sentalo leaves are simply ground and then placed on the torn wound. Apart from being an antibacterial, sentalo leaves also have the potential as antidiabetic. The application of the sentalo leaf is expected to be more efficient, easy to apply by the community in health services for people with diabetes mellitus. The design of this study was True Experimental with treatment using RAL (Completely Randomized Design) and data analysis using the one-way ANOVA test. The results of the analysis of the antidiabetic effectiveness of sentalo leaf tea were shown by looking at the significant value of the one-way Anova test of 0.000 < 0.05 which could be concluded that there was a difference in the antidiabetic activity of sentalo leaf tea. The difference in blood glucose reduction in the treatment with Glibenclamide as a control group with Sentalo leaf tea 250 mg/kgBW was the same and not significant. So, it can be concluded that the optimum dose of sentalo leaf tea to obtain effective antioxidant activity is 250 mg/kgBB